2004
DOI: 10.1111/j.1349-7006.2004.tb03327.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of cell cycle regulatory proteins and MAP kinase signaling pathway in growth inhibition and cell cycle arrest by a selective cyclooxygenase 2 inhibitor, etodolac, in human hepatocellular carcinoma cell lines

Abstract: yclooxygenase 2 (COX-2) is a highly inducible, rate-limiting enzyme involved in the production of prostaglandins (PGs), prostacyclins and thromboxanes. COX-2 is expressed in response to a variety of proinflammatory agents and cytokines.1, 2) Overexpression of COX-2 has been demonstrated in various tumors such as colon cancer, pancreatic cancer and hepatocellular carcinoma (HCC).3-5) Nonsteroidal anti-inflammatory drugs (NSAIDs) are currently being assessed for use in the prevention and treatment of colorectal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 34 publications
(43 reference statements)
8
33
0
Order By: Relevance
“…We found that treatment with NS398 alone decreased cyclin E expression in a concentration-dependent manner. This effect of NS398 may not be common to all COX-2 inhibitors, as Cheng et al reported that treatment with the selective COX-2 inhibitor etodolac did not alter cyclin E expression (62). We also observed that the effects of the combination on cyclin E levels were similar to the effects of the single agents.…”
Section: Mol Cancer Res 2006;4(6) June 2006supporting
confidence: 60%
“…We found that treatment with NS398 alone decreased cyclin E expression in a concentration-dependent manner. This effect of NS398 may not be common to all COX-2 inhibitors, as Cheng et al reported that treatment with the selective COX-2 inhibitor etodolac did not alter cyclin E expression (62). We also observed that the effects of the combination on cyclin E levels were similar to the effects of the single agents.…”
Section: Mol Cancer Res 2006;4(6) June 2006supporting
confidence: 60%
“…Although the mechanism by which inhibition of cyclins A and B and, therefore, G 2 arrest by OSU-03012 remains uncertain, this may be related to a possible effect on the MAPK signaling pathway evidenced by the down-regulation of p-MEK1/2 and MEK1/2. In this respect, the selective COX-2 inhibitor, etodolac, was recently reported to induce G 2 arrest in human hepatocellular carcinoma cell lines through the inhibition of expression of cyclins A and B due to an effect on the MAPK signaling pathway, without inhibition of the PDK-1/Akt pathway (45). Of note, however, although cyclin D1 was significantly down-regulated, no significant G 1 -S phase arrest was observed.…”
Section: Discussionmentioning
confidence: 76%
“…However, the key mechanism by which COX-2 inhibitors affect HCC cell growth remains unclear. Some studies have shown that NSAIDs are able to inhibit HCC cell growth by cell cycle arrest [72,73,75] , induction of apoptosis [44,73,74] or necrosis [72] . Recent evidence indicates that phar macological inhibition of COX-1 activity by selective COX-1 inhibitors also blocks cell growth, promotes apoptosis and inhibits the cell cycle in ovarian [57] , breast [76] , bladder and prostate [77] cancer cells.…”
Section: Cox Inhibitors In Hepatocellular Carcinomamentioning
confidence: 99%